Effects of genotypes on sperm quality and fertility of buffalo bulls - Miraz, Md Faizul Hossain; Deb, Gautam Kumar; Hossain, Sheikh Mohammad Jahangir; Akter, Shahrina (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: The objective of this study was to evaluate the effects of genotypes on semen quality and fertility of Murrah, Nili-Ravi, and Bangladeshi indigenous buffalo bulls. Materials and Methods: Fresh semen was collected from pure Murrah, Nili-Ravi, and indigenous buffalo bulls. Sperm concentration, motility, morphology, kinematics, and dose/ejaculation were assessed by a computer-assisted sperm analyzer. Fresh semen was cryopreserved, and post-thaw semen quality and fertility were evaluated. The hypoosmotic swelling test (HOST) was used to evaluate plasma membrane integrity. Results: Indigenous bulls produce a lower volume of semen but exhibit higher total motility than Murrah and Nili-Ravi bulls. After cryopreservation, the post-thaw motility remains consistent, except for significant motility losses observed in Nili-Ravi bulls. Nili-Ravi bulls also showed a higher incidence of bent and coiled tails, while indigenous bulls exhibited significantly lower percentages of distal droplets than the others. Static sperm have significantly smaller head width, head elongation, and head area, and higher tail straightness than motile and progressively motile sperm. Fresh indigenous bull sperm have higher average path velocity, straight linear velocity, curvilinear velocity, and linearity than others. The Nili-Ravi bull has significantly lower HOST-positive sperm than others in fresh and post-thaw conditions. Genotypes did not exhibit any significant differences in dose/ejaculation and fertility rate. Conclusion: Indigenous bulls exhibit superior semen quality in motility, plasma membrane integrity, and post-thaw viability compared to Murrah and Nili-Ravi bulls. Additionally, the higher progressive motility and improved kinematic properties observed in indigenous bulls may have contributed to their higher fertility rates. However, no significant differences in fertility outcomes were found among the genotypes, suggesting that all three genotypes performed similarly in terms of fertility through artificial insemination (AI), at least under on-station conditions. Further research needs to be carried out to evaluate AI efficiency and fertility rate under on-farm conditions. J. Adv. Vet. Anim. Res., 12(3): 1019–1029, September 2025 http://doi.org/10.5455/javar.2025.l961